Pengaruh Ekspor Komoditi Kelapa Sawit dan Karet terhadap Pertumbuhan Ekonomi di Pulau Sumatera - Dwi Fuji Cahyanti; Yulhendri Yulhendri (Jurnal Ecogen, 2022)
This research aims to see 1) The Effect of Palm oil Commodity Exports on Economic Growth on the Island of Sumatra, 2) The Effect of Rubber Commodity Exports on Economic Growth on the Island of Sumatra, 3) The influence of palm oil and rubber commodity exports on economic growth on the island of Sumatra. This is a quantitative research. The data used is secondary data with the type of panel data from 2011-2019, obtained from the relevant agencies. This study uses panel data analysis techniques using the Common Effect Model, Fixed Effect Model, and Random Effect Model with the estimation method of Chow test, Hausman test, and Langrange Multiplier test. While testing the hypothesis using t-test and f-test. The data collection technique used is literature study and documentation. The results of the study show 1) The export of palm oil commodities has a negative and significant effect on economic growth on the island of Sumatra from 2011-2019, 2) Palm oil exports have a positive and significant impact on economic growth on the island of Sumatra from 2011-2019, 3) Overall together, palm oil exports and rubber exports have an effect on economic growth on the island of Sumatra from 2011-2019. Keywords : palm oil export, rubber export, economic growth